Pressure pain threshold of the mastigatory muscles and reaction to touch in adults with down syndrome and neurotypicals: cross-sectional study - Zuanon, Letícia Abdelnour [UNESP]; Líbera, Juliana Dela [UNESP]; Rodrigues, João Victor Soares [UNESP]; Petrilli, Pedro Henrique [UNESP]; Horikawa, Alexia Ribeiro [UNESP]; dos Santos, Márcio José Possari [UNESP]; Theodoro, Letícia Helena [UNESP]; Turcio, Karina Helga Leal [UNESP] (Elsevier, 2024)
Background: Down Syndrome (DS) is currently the most common chromosomal condition associated with intellectual disability in the global population and is characterized by a variety of additional clinical findings. Individuals with DS may exhibit altered perception and reaction to painful stimuli, which makes the diagnosis of pain in DS a challenge. This study aimed to evaluate the pressure pain threshold of the masticatory muscles and the reaction to social touch in individuals with DS compared to neurotypical individuals (NT). Methods: Patients with DS and NT individuals were included following predefined inclusion criteria. The assessment and comparison methods used between the groups were: 1) Algometry to quantify the pressure pain threshold of the masseter, temporal, and abductor pollicis brevis; 2) Social Touch Questionnaire (STQ) to assess social touch acceptance. Data obtained from the assessments were submitted to normality tests to determine if they followed a normal distribution. The Pressure Pain Threshold data were analyzed using the Mann-Whitney test, while the Social Touch data were analyzed using the student's t-test, both with a significance level of 5%. Results: A total of 32 patients were included in the study, sixteen with DS and sixteen NT individuals. The results showed that the pressure pain threshold of all analyzed muscles in the DS group was significantly higher (p < 0.001) than in the NT group. However, social touch acceptance was similar between the two groups (p = 0.270). Conclusions: It was concluded that the pressure pain threshold is significantly higher in individuals with DS compared to NT, but social touch acceptance is similar between the groups.
Keywords: Down syndrome; Pain threshold; Sensory function